Do office tyrants and centralized decision making drive workplace creative behaviours? - Li, Ci‐Rong; Lin, Chen‐Ju; Pauleen, David (Creativity and innovation management, 2024)
Based on affective events theory and the cognitive–affective processing system, this study explores indirect positive and negative effects of perceived abusive supervision on employee creativity through employees' affective reactions at work and how the centralization of decision making can moderate the associations between employee‐perceived abusive supervision and anxiety/anger. Using a cross‐lagged panel method to collect an effective sample of 200 employee participants which provided three‐week survey data, we tested causality between research variables with a structural equation modelling analysis using Mplus 8.0. The findings showed that a positive effect on employee creativity may occur when an employee experiences anxiety rather than anger when subject to abusive supervision. In addition, the influence of employee‐experienced abusive supervision on employee anger increases when the organization has highly centralized decision making, which hinders employees' creative performance. Theoretically and practically, this study contributes interesting and somewhat conflicting views to three areas of management literature—abusive supervision, employees' affective reactions and creativity management—including challenging the supposition that only uplifting styles of leadership can encourage employees to create new ideas.